Enhancing Students' Learning Interest Through the Implementation of the Kampus Mengajar Batch 8 Program: Classroom Arrangement - Refi; Indriyani; Karim, Rahmat (Digital Innovation, 2024)
Currently, with the allocation of school funds from the government, access to improving school quality has become an interesting topic to discuss. Both in terms of knowledge and school environmental management. As with most schools in general, the majority of school funds are used for physical development, such as an attractive classroom arrangement program. The class 8 teaching campus located in Banu-Banua Jaya village will organize classroom arrangements. The expected impact after this activity is the creation of a comfortable and attractive classroom. Based on the results of the activities that have been carried out, it can be concluded that the guidance material for developing literacy and numeracy-based classroom models for elementary schools is declared valid with a score of 90.6%, although there are deficiencies in the explanation of implementation procedures. Revisions based on expert literature input have been carried out, and validation results from spatial planning experts, school principals, and field trials show excellent feasibility with the highest score of 97.2%. Class 8 Teaching Campus Program activities, collaboration between teaching campus students. 8 and the principal of SD 1 Banu-Banua Jaya have run well and are able to provide comfort when studying and increase students' interest in learning with a pleasant classroom atmosphere.